A fully coupled mechano-electrochemical model for all-solid-state Li-ion batteries: An optimal strategy for controlling interfacial contact using internal stress generated by electrode expansion. (1st March 2023) - Shao, Yu-qiang; Liu, Huan-ling; Shao, Xiao-dong; Sang, Lin
Abstract: A fully coupled electrochemical-mechanical model of all-solid-state Li-ion batteries (ASSLBs) considering the interfacial contact loss is established. The influences of current and partial molar volume of cathode/anode on the interfacial contact and performance of the ASSLB are numerically studied. The results show that the range of stress changes within the ASSLB are dependent on the current applied. Lithium (Li) partially inserted into anode cannot return to cathode during discharging, which causes a "residual stress" and then can improves the interface contact. The interfacial contact loss gives rise to an increase in local current density. Cycling with a current density of 0.2 mA cm −2, the local current density across the electrode/electrolyte interface is as high as 0.66 mA cm −2, which increases risks such as dendrite formation. We further show that a large partial molar volume of cathode/anode may directly reduce the capacity retention. Moreover, higher partial molar volume of cathode or lower that of anode reduces the (stack) stress, which can deteriorate the interface contact area. Finally, the cathode materials with lower partial molar volume are recommend to balance capacity and interfacial contact. As for anodes, the moderate partial molar volumes are required for robust ASSLBs with improved performance characteristics.